(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hepatitis B virus (HBV) is a globally significant pathogen responsible for chronic liver infection, cirrhosis, and hepatocellular carcinoma. In Pakistan, where approximately 3% of the population is affected, HBV is considered endemic. Key risk factors include unsafe medical practices, needle reuse, and poor hygiene in healthcare and community settings. This study aimed to assess the correlation between HBV DNA quantification using real-time PCR and two chemiluminescence immunoassay (CLIA)-based serological markers—hepatitis B e antigen (HBeAg) and anti-hepatitis B e antibodies (Anti-HBeAb)—among patients with chronic hepatitis B in District Swabi, Pakistan. A total of 100 serum samples were collected from patients diagnosed with chronic hepatitis B at tertiary and rural healthcare centers. HBV DNA levels were measured using real-time PCR, while HBeAg and Anti-HBeAb levels were analyzed using CLIA. Most patients (89%) exhibited low HBeAg titers (1.6–5.0 IU/mL), suggesting minimal viral replication. Only a small proportion showed moderate (5–10 IU/mL; 2%), strong (20.1–30.0 IU/mL; 3%), or very strong (>30 IU/mL; 1%) reactivity. Anti-HBeAb was commonly detected, indicating potential viral seroconversion. The correlation between HBeAg and HBV DNA levels was found to be variable, with weak concordance in several cases. CLIA-based detection of HBeAg and Anti-HBeAb may serve as a cost-effective alternative to molecular assays in low-resource settings. However, due to their limited predictive value for viral load, they are best used in conjunction with molecular diagnostics for accurate disease staging and treatment monitoring.